2006
DOI: 10.1248/bpb.29.2070
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Tumor Cells by Three Naphthoquinone Esters Isolated from Thai Medicinal Plant: Rhinacanthus nasutus KURZ.

Abstract: Cancer causes significant morbidity and mortality and is a major public problem world widely. Cancer chemotherapy, a routine method for the treatment in cancer patients, faces on the problems of unstable efficiency, severe side effects, and cost. Therefore, new drugs with high efficacy without severe side effects, along with understanding the molecular basis in cancer treatment, are awaited.Many attentions have been focused on natural products as potential sources of novel anticancer drugs over the decades. 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 35 publications
(69 reference statements)
0
35
0
Order By: Relevance
“…Rhinacanthins-C, -N and -Q isolated from dried roots of Rhinacanthus nasutus, a plant traditionally used in Thai folk medicine for treating various cancers including cervical and hepatocellular cancers, has been shown to suppressed HeLa cells through induction of apoptosis by activation of caspase-3 pathway (Siripong et al, 2006a). The same group have also shown that when these naphthoquinone esters are liposomalized with egg yolk phosphatidylcholine (EPC) and egg yolk phosphatidylglycerol (EPG), there was significant increase in the antiproliferative effects on HeLa cells as measured by cell proliferation assay (Siripong et al, 2006b).…”
Section: Naphthoquinone Estersmentioning
confidence: 99%
“…Rhinacanthins-C, -N and -Q isolated from dried roots of Rhinacanthus nasutus, a plant traditionally used in Thai folk medicine for treating various cancers including cervical and hepatocellular cancers, has been shown to suppressed HeLa cells through induction of apoptosis by activation of caspase-3 pathway (Siripong et al, 2006a). The same group have also shown that when these naphthoquinone esters are liposomalized with egg yolk phosphatidylcholine (EPC) and egg yolk phosphatidylglycerol (EPG), there was significant increase in the antiproliferative effects on HeLa cells as measured by cell proliferation assay (Siripong et al, 2006b).…”
Section: Naphthoquinone Estersmentioning
confidence: 99%
“…With respect to the naphthoquinone benzoate esters (7-9 and 13-15), the OH and OMe groups on the benzoate part of 2 0 -cyclopentyl naphthoquinone esters 8 and 9 conferred less activity against all three tested cancer cell lines than the one with no C-1 substitution (7) which corresponds to the analogues of the 2 0 ,2 0 -dimethyl naphthoquinone esters in our previous work. 1) In contrast, an OH group Esters 7,9,10,12,13,15,16,and 18.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…7) Liposomal formulations of rhinacanthins have been studied and showed strong antiproliferative activity against HeLaS3 cells. 8) Moreover, apoptosis induction by rhinacanthones 9) and rhinacanthins 10) has also been investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports of investigation states that leaves and stems of R. nasutus contains various types of flavonoids, benzenoids, coumarin, anthraquinone, quinone, glycosides, carbohydrate, triterpenes, sterols, and chlorophyll [5]. The naphthoquinone; rhinacanthins (A-D, G-Q), rhinacanthone and lignan groups are the main bioactive compounds [6]. The leaf petroleum ether fraction shows significant mosquitocidal activity [7].…”
Section: Introductionmentioning
confidence: 99%